Optimization Design and Simulation of Adjusting Mechanism for Wall-press Oil and Gas In-pipe Robot - Yang Caixia; Li Jianjun; Sun Weihong; Xu Xiaodong (Jixie chuandong)
To improve the performance of adjusting performance for wall-press oil and gas in-pipe robot,part of the in-pipe robot adjusting mechanism is parametric modeled and optimization designed through ADAMS. The integrated adjusting mechanism model is set up by Solid Works according to the optimized data and the structure characteristics of adjusting mechanism for in-pipe robot,then imports the model and makes simulation analysis in ADAMS. The optimized nut horizontal thrust is reduced 41. 5%,besides,the impact load which acts on adjusting mechanism of in-pipe robot is simulated,the influence of the horizontal thrust and changes in the situation of compression spring when the adjusting mechanism is in the process of adjusting or suffering impact load is separately obtained,the theoretical basis for the selection of suitable motor and the compression spring is provided.